Multidimensional Approaches to Examining Digital Literacies in the Contemporary Global Society - Lee, Kewman M. (2019)
Literacy scholars have offered compelling theories about and methods for understanding the digital literacy practices of youth. However, little work has explored the possibility of an approach that would demonstrate how different perspectives on literacies might intersect and interconnect in order to better describe the multifaceted nature of youth digital literacies. In this conceptual article, we adopt the idea of theoretical triangulation in interpretive inquiry and explore how multiple perspectives can jointly contribute to constructing a nuanced description of young people’s literacies in today’s digitally mediated global world. For this purpose, we first suggest a triangulation framework that integrates sociocultural, affective, and cognitive perspectives on digital literacies, focusing on recent developments in these perspectives. We then use an example of discourse data from a globally connected online affinity space and demonstrate how our multidimensional framework can lead to a complex analysis and interpretation of the data. In particular, we describe the substance of one specific case of youth digital literacies from each of the three perspectives on literacy, which in turn converge to provide a complex account of such literacy practices. In conclusion, we discuss the promise and limitations of our integrative approach to studying the digital literacy practices of youth.